Ensuring business continuity during a pandemic - Мехед, Дмитро Борисович; Мехед, Катерина Миколаївна; Шелест, Михайло Євгенович (Ukrainian Information Security Research Journal, 2020)
Business continuity is a priority for participants in the financial sector and financial authorities. Business continuity management, an important component of operational risk management, is an approach that covers all aspects of the business and includes policies, standards and procedures to ensure or timely resumption of certain business operations in case of disruption in business continuity. The goal of the management is to minimize the consequences of violation – operational, financial, legal, material consequences, as well as damage to reputation, etc. Effectively manage business continuity, in which special attention is paid to the nature of the impact, and not to the source of the violation. This allows participants in the financial sector and financial authorities to have more room to maneuver in the event of various violations. At the same time, organizations cannot ignore the nature of the risks they face. Effective business continuity management usually includes analyzing the impact of various events on business continuity, choosing a recovery strategy and drawing up a business continuity plan, as well as providing audit programs, staff training and information programs, as well as information exchange and crisis management programs. It is impossible to predict the next crisis, but you can prepare for it. Failures of established business processes can affect an organization of any scale, regardless of country. Natural disasters, interruptions in the supply of electricity, political instability and even an epidemic of the virus - each organization should have a plan "B", which will ensure the continuity of its work in any unforeseen situation. We are amidst a global pandemic. The coronavirus COVID-19 has been spreading like wildfire across geographies affecting people’s health and well-being. To contain its spread, many organizations in both the private and public sector have encouraged – and in some parts of the world enforced – their employees to work from home. This includes IT staff that vigilantly care for our datacenters.